Pengaruh penerapan green accounting dan komite audit terhadap profitabilitas pada perusahaan basic materials yang terdaftar di Bursa Efek Indonesia - Sabet Tina Sibarani; Riky Sai Maruli; James Uly Reke (LPMP Imperium, 2026)
This study aims to analyze the influence of Green Accounting and Audit Committees on the profitability of Basic Materials companies listed on the Indonesia Stock Exchange for the 2021–2024 period. The study population consisted of 113 companies. The raw materials sector experienced 10 delistings during the research period. Based on purposive sampling criteria, 93 companies that did not experience delistings during the study period were selected. Over 4 years, the total sample size was 372. GA was measured using the ratio of Net Income to Environmental Expenses. At the same time, the Audit Committee was proxied by the number of audit committee members listed in the company's annual report. Company profitability was measured using ROA. The analysis method was a quantitative, multiple linear regression approach. The results showed that GA had no significant effect on company profitability. Similarly, the Audit Committee, measured by the number of members, did not significantly influence ROA. Simultaneously, these two independent variables also had no significant effect on profitability. Public interest statements This research reveals that implementing green accounting and having an audit committee do not always directly increase profitability. Therefore, an optimal implementation is needed to improve performance and enhance the company's competitiveness.